Digital Health Literacy And Adherence To Type 2 Diabetes Mellitus Management: A Cross-Sectional Study At Mojolangu Community Health Center - Bulandari; Abdul Qodir; Waifti Amalia (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
While digital health literacy (DHL) is crucial for type 2 diabetes mellitus (T2DM) self-management, evidence in primary care settings remains limited. This quantitative cross-sectional study aimed to examine the association between DHL and T2DM management adherence among 115 patients (aged 35–65 years) at Mojolangu Community Health Center. Data were collected using the Electronic Health Literacy Scale (eHEALS) and the Indonesian Diabetes Self-Management Instrument (IDN-DSMI). Spearman's rank correlation analysis revealed a significant positive association between DHL and management adherence (r = 0.622, p < 0.001). In conclusion, higher digital health literacy is associated with better management adherence, suggesting that strengthening DHL may improve patients' self-management capabilities and long-term health outcomes.